Transposition burst of mariner-like elements in the sequenced genome of Rhodnius prolixus. (February 2016) - Fernández-Medina, R.D.; Granzotto, A.; Ribeiro, J.M.; Carareto, C.M.A.
Abstract: Transposable elements (TEs) are widespread in insect's genomes. However, there are wide differences in the proportion of the total DNA content occupied by these repetitive sequences in different species. We have analyzed the TEs present in R. prolixus (vector of the Chagas disease) and showed that 3.0% of this genome is occupied by Class II TEs, belonging mainly to the Tc1-mariner superfamily (1.65%) and MITEs (1.84%). Interestingly, most of this genomic content is due to the expansion of two subfamilies belonging to: irritans himar, a well characterized subfamily of mariners, and prolixus1, one of the two novel subfamilies here described. The high amount of sequences in these subfamilies suggests that bursts of transposition occurred during the life cycle of this family. In an attempt to characterize these elements, we performed an in silico analysis of the sequences corresponding to the DDD/E domain of the transposase gene. We performed an evolutionary analysis including network and Bayesian coalescent-based methods in order to infer the dynamics of the amplification, as well as to estimate the time of the bursts identified in these subfamilies. Given our data, we hypothesized that the TE expansions occurred around the time of speciation of R. prolixus around 1.4 mya. This suggestion lays on the "Transposon Model" of TE evolution, in which the members of a TE population that are replicative active are present at multiple loci in the genome, but their replicative potential varies, and of the "Life Cycle Model" that states that when present-day TEs have been involved in amplification bursts, they share an ancestral copy that dates back to this initial amplification. Graphical abstract: Highlights: Great variability of Tc1/mariner subfamilies in the R. prolixus genome. Burst of transposition of three subfamilies of mariner elements. Transposition bursts temporally related with the speciation event that resulted in the diversification of R. prolixus from a R. prolixus/robustus ancestor, 1.4 mya.